A new motor synergy that serves the needs of oculomotor and eye lid systems while keeping the downtime of vision minimal - Khazali, Mohammad Farhan; Pomper, Joern K; Smilgin, Aleksandra; Bunjes, Friedemann; Thier, Peter (eLife, 2016)
The purpose of blinks is to keep the eyes hydrated and to protect them. Blinks are rarely noticed by the subject as blink-induced alterations of visual input are blanked out without jeopardizing the perception of visual continuity, features blinks share with saccades. Although not perceived, the blink-induced disconnection from the visual environment leads to a loss of information. Therefore there is critical need to minimize it. Here we demonstrate evidence for a new type of eye movement serving a distinct oculomotor demand, namely the resetting of eye torsion, likewise inevitably causing a loss of visual information. By integrating this eye movement into blinks, the inevitable down times of vision associated with each of the two behaviors are synchronized and the overall downtime minimized.
Keywords: eye movements; vision stability; blinking; vision suppression